Productivity and Quality of Facilities and Infrastructure as Support for RRI Tolitoli Broadcasting - Zulfikar; Iqbal, Muhammad; Nursifa; Makmur, Syarif (Teras Kampus, 2024)
This research aims to answer the basic problems faced by Radio Republik Indonesia (RRI) Tolitoli in increasing the productivity and quality of broadcasting facilities and infrastructure. Using a qualitative approach and descriptive research methods, this research was conducted at the Republic of Indonesia Radio Public Broadcasting Institute (LPP RRI) Tolitoli over a three-month period. Primary data was obtained through direct observation and in-depth interviews with six informants selected purposively. The research results show that RRI Tolitoli faces a number of challenges in increasing productivity and broadcast quality, especially related to poor infrastructure conditions. Through analysis of productivity and quality variables, research findings highlight the need for improvements in technical and managerial aspects. Although RRI Tolitoli has demonstrated a strong commitment to providing quality broadcasting services, there is still room for significant improvement in terms of technical infrastructure and resource management. The recommendations resulting from this research can become the basis for continuous improvement efforts in public broadcasting in Indonesia, with the main aim of meeting public demands for broadcasting that is informative, high quality and has a positive impact.